Climate-smart agriculture in South Asia: opportunities and constraints in scaling out [Abstract only] - Aggarwal, Pramod K. (2015)
South Asia comes across as amongst the most vulnerable regions to climate change in the Inter-government Panel on Climate Change (IPCC)’s Fifth Assessment Report released a year ago, and in other similar reports. Climate change in the region is manifested by depleting glaciers, increasing coastal erosion, frequent heat waves, rising sea level, frequent floods and droughts and varying rainfall patterns. It is now evident that South Asia’s climate is already changing and the impacts are already being felt. As a largely agrarian economy, this vulnerability is compounded by the fact that more than 700 million people’s livelihoods depend on agriculture directly influenced by changes in climate. Although South Asia has seen robust economic growth, with the GDP averaging about 6 percent over the past 20 years, the region is still home to 1/4th of the world’s hungry and 40% of the world’s malnourished children and women. As populations continue to rise and the demand for food grows, the question is: how will this increase in demand be met and where will all this food be grown? With stiff competition for land from the non-farm sector, expanding farmlands is not an option. Climate change will further exacerbate the existing pressures on land and water resources. If the second Sustainable Development Goal of ending poverty, achieving food security and promoting sustainable agriculture is to be realised, climate change adaptation and mitigation technologies, practices, services and policies will need to be implemented in earnest. Many recent studies show a probability of 10-40 percent loss in crop production by 2070-2100 on account of rising temperatures and decrease in irrigation water, unless steps are initiated now to increase our adaptive capacity. For example, even with the benefits of carbon fertilization (which could anyway be negatively affected by increase in surface ozone concentration) India stands to lose nearly 4-5 tonnes of wheat with every rise in temperature of 1 degree Celsius. This estimate could be even higher when decrease in irrigation is factored in. Wheat losses could be significant even in the short term, while losses for other crops are uncertain and estimated to be relatively smaller, particularly so for monsoon crops. Similarly, there are studies to show that livestock and fish productivity could also decline. Climate change does offer some opportunities as well. One adaptive measure is to identify regions that would become conducive for certain crops in the changed climate. For example, farmers in the upper regions of Himachal Pradesh in India have taken to growing apples because temperatures in the lower regions became too warm for its growth. The shift in cultivation brought new opportunities and high incomes for these farmers while their counterparts in the south switched to cultivating vegetables. It is clear that per hectare cultivation of food needs to drastically increase to meet growing food demands. While this is a challenge, the existing large crop yield gaps in the region suggest there is potential to increase crop production per hectare even in the face of increasing climatic risks. For this to happen, investments in land and water management, infrastructure, and research accompanied by enabling policies, sustained regional cooperation and robust institutions is crucial. Increased production variability could perhaps be the most significant impact of global impact change in Asian countries. Short-term changes in weather extremes, which are still not very predictable in most countries of the region, pose huge challenges. Some recent examples are the drought in 2014, the floods in Pakistan in 2010, floods in India, Nepal and Bangladesh in 2007 and the heat-stress experiences in India in 2004 which resulted in fluctuating yields, food price volatility and threatened food security and incomes. Such volatility is despite the vast irrigation network in the region, especially in the Indo-Gangetic plains. During last few decades, excessive groundwater extraction has resulted in widespread decline in water table and water quality degradation. To ensure future food security in climate change scenarios, investment in managing and stabilizing the existing irrigated potential while exploring options to expand this potential is the need of the hour. Several technological, institutional and policy interventions have been proposed that can help us adapt to climate change as well as to current and future weather variability. These include simple adaptation practices such as changes in planting dates and crop varieties. Additional strategies that have been proposed include: the deployment of adverse climate tolerant genotypes and diversified land use systems, the use of solar irrigation, assisting farmers in coping with current climatic risks through providing weather linked value-added advisory services and crop/weather insurance, and improved land and water use management and policies. Agriculture in South Asia contributes between 15-20 percent to total greenhouse gas emissions. These are primarily from enteric fermentation in ruminant animals, rice paddy cultivation, and nitrous oxide from manures and fertilizers application to soils. What is interesting to note is that most of the proposed adaptation options, if implemented scientifically, come with large mitigation co-benefits. CCAFS is scaling out the Climate-Smart Villages (CSVs) model in several countries, including in South Asia, to promote climate-smart agriculture (CSA). Climate Smart Villages are sites where a portfolio of the most appropriate technological and institutional interventions, determined by the local community, are implemented to increase food production, enhance adaptive capacity and reduce emissions. Interventions are bespoke to each village but the concept lends itself to be applied in any region under the right circumstances. Initial results suggest a large potential to maximise synergies among different interventions in order to scale out CSA. Much work needs to be done to expand the evidence base of CSVs with regard to targeting the approach in different agro-climates, the costs: benefit analysis in terms of investment and returns, and the institutional and policy changes that are needed to promote CSA. In the South Asia region, problems of widespread poverty, poor governance, weak institutions, and human capital limit agricultural growth today. These problems can also reduce the potential of adaptation strategies. It is critical to simultaneously address these political and socio-economic constraints if the full potential of CSA is to be realised for farmers and the region as a whole.